Political Ideology and Judicial Decision-Making in Contemporary Legal Systems - Hermawan, Asep (Politeknik Siber Cerdika Internasional, 2025)
Background: Judicial decision-making has long been regarded as a neutral and objective process grounded in legal reasoning and precedent. Nevertheless, a growing body of empirical and socio-legal scholarship suggests that political ideology may shape judicial behavior, particularly in cases involving constitutional interpretation, civil rights, and public policy. This debate raises important questions regarding judicial impartiality and the integrity of the rule of law. Objective: This study aims to examine the extent to which political ideology influences judicial reasoning and decision-making processes, as well as to identify how institutional structures and external political pressures mediate such ideological effects. Methods: The research employs a qualitative approach through doctrinal and comparative legal analysis. Judicial opinions, constitutional case law, and scholarly commentaries from high courts across multiple jurisdictions are systematically analyzed. The study focuses on decisions related to constitutional rights, administrative law, and social justice issues to identify recurring ideological patterns in judicial interpretation. Results: The findings reveal discernible ideological tendencies in judicial rulings. Judges with conservative orientations tend to adopt more restrictive interpretations of statutes and constitutional provisions, while judges with liberal orientations are more inclined toward expansive interpretations, particularly in cases involving civil liberties and regulatory governance. Additionally, institutional arrangements and political environments influence the extent to which ideological preferences are reflected in judicial outcomes. Conclusion: This study concludes that although judicial decisions are formally grounded in legal doctrine, political ideology remains an underlying factor shaping legal interpretation. Recognizing these dynamics is essential for promoting transparency, judicial accountability, and public trust in the judiciary. The findings contribute to broader discussions on judicial behavior and underscore the importance of safeguarding impartiality within democratic legal systems.